Enhancing Writing Ability Through Idea Listing Technique - Miftah, M. Zaini (Universitas Islam Negeri (UIN) Syekh Wasil, Kediri, Indonesia, 2015)
The study is aimed at developing the Idea Listing Technique (ILT) to enhance the students‟ writing ability. The Classroom Action Research was applied in this study. The subjects of the study were 31 students, the students taking the course of Writing II, of the third semester of English Department of one State Islamic College at Palangka Raya, Indonesia, in the 2012/2013 academic year. The findings show that the implementation of ILT can enhance the students' ability in writing expository paragraph. It is indicated by the enhancements of the percentage of the students achieving the score greater than or equal to C (60-69), and of the percentage of their involvement in the writing activities during the implementation of ILT in Cycle I and II. Thus, the enhancement of the students' ability in writing expository paragraph can be reached but it should follow the appropriate procedures of the implementation of ILT having been developed.